Bamboo Wine from Oxytenanthera braunii - Mgeni, A. S. M. (Indian Forester, 1983)
Oxytenanthera braunii is a bamboo species belonging to the genera of Bambusaceae. It is cultivated in some highland areas of Tanzania mainly for the bamboo wine production during the rain season. The wine is very popular with rural population and low urban income earners. It is a source of income to both families and village governments. Moreover, it is used as a refreshment to participants in co-operative farming. More important, the availability of bamboo wine saves some cereals that would have been used in local alcohol brewing for food. The species is propagated by planting the detached two year old rhizome including its culm within the first month of the rain season.